The Receptor for Advanced Glycation End Products (Rage) and Its Ligands in Plasma and Infrainguinal Bypass Vein. Issue 4 (April 2016) - Malmstedt, J.; Frebelius, S.; Lengquist, M.; Jörneskog, G.; Wang, J.; Swedenborg, J.
Abstract : Objective: The aim was to investigate whether RAGE and its ligands are associated with infrainguinal bypass outcome in patients with and without diabetes. Methods: This was a prospective observational cohort. Patients ( n  = 68) with ( n  = 38) and without ( n  = 30) diabetes undergoing infrainguinal vein bypass for peripheral arterial disease were followed for 3 years. Endosecretory RAGE (esRAGE), S100A12, advanced glycation end products, and carboxymethyl-lysine (CML) were determined in plasma using ELISA. The influence of plasma levels on the main outcome (amputation free survival) was evaluated using Cox proportional hazard analysis. Plasma esRAGE, CML, and S100A12 in healthy controls ( n  = 30) without cardiovascular disease matched for sex and age were compared with patients, using the Mann–Whitney U test. Veins from bypass surgery procedures were stained and S100A12, RAGE, AGE, and CML were determined using immunohistochemistry. Results: Forty-six patients survived with an intact leg during follow up. Seventeen died (median survival time 702 days, IQR 188–899 day), and six had amputations. High plasma S100A12 was associated with reduced amputation free survival (hazard ratio [HR] 2.99; 95% CI 1.24–7.24) when comparing levels above the 75th percentile with levels below. The increased risk was unchanged adjusting for age, sex, and diabetes. Diabetic patients had higher plasma S100A12 (11.75 ng/mL; 95% CI 8.12–15.38 ng/mL) than non-diabetic patients (5.0141 ng/mL; 95% CI 3.62–6.41 ng/mL), whereas plasma CML, esRAGE, and AGE were similar. Plasma CML and S100A12 were higher in patients than in controls (1.25 μg/mL, 95% CI 1.18–1.32 μg/mL vs. 0.8925 μg/mL, 95% CI 0.82–0.96 μg/mL; and 8.7 μg/mL, 95% CI 6.52–10.95 μg/mL vs. 3.47 μg/mL, 95% CI 2.95–3.99 μg/mL, respectively). The proportion of vein tissue stained for AGE (21%), RAGE (5%), CML (9%) and S100A12 (3%), were similar in patients with and without diabetes. Conclusions: Plasma S100A12 and CML are elevated in peripheral arterial disease and markers of RAGE and its ligands are found in vein used for bypass. This indicates a role for S100A12, CML, and RAGE in peripheral arterial disease complications by activation of the RAGE system.